Genomics insights into a Mycobacterium pinnipedii isolate causing tuberculosis in a captive South American sea lion (Otaria flavescens) from Italy - Alba, Patricia; Caprioli, Andrea; Cocumelli, Cristiano; Eleni, Claudia; Diaconu, Elena Lavinia; Donati, Valentina; Ianzano, Angela; Sorbara, Luigi; Stravino, Fiorentino; Cerini, Natalino; Boniotti, Maria Beatrice; Zanoni, Mariagrazia; et al. (Frontiers in Microbiology, 2023)
Tuberculosis (TB) affects humans and other animals, and it is caused by bacteria within the Mycobacterium tuberculosis complex (MTBC). In this study, we report the characterisation of Mycobacterium pinnipedii that caused a TB case in a sea lion (Otaria flavescens) kept in an Italian zoo. The animal died due to severe, progressive disorders involving the respiratory and gastro-enteric systems and the skin. At necropsy, typical gross lesions referable to a TB generalised form were found. In particular, nodular granulomatous lesions were detected in the lungs and several lymph nodes, and colonies referable to Mycobacterium spp. were isolated from lung, mesenteric, and mediastinal lymph nodes. The isolate was identified by PCR as a MTBC, had a spoligotype SB 1480 (“seal lineage”), and was characterised and characterised by whole-genome sequencing analysis confirming that the MTBC involved was M. pinnipedii. The analysis of the resistome and virulome indicated the presence of macrolide and aminoglycoside resistance genes intrinsic in M. tuberculosis [erm-37 and aac(2′)-Ic] and confirmed the presence of the region of difference 1 (RD1), harbouring the esxA and esxB virulence genes, differently from its closest taxon, M. microti. As for other MTCB members, M. pinnipedii infection can spill over into non-pinniped mammalian species; therefore, zoological gardens, veterinary practitioners, and public health officers should be aware of the hazard posed by tuberculosis from marine mammals. Since the isolate under study, as well as all available genomes of M. pinnipedii investigated in this study retains almost all the M. tuberculosis virulence genes, it could indeed cause infection, lesions, and disease in other animal species, including humans.